A cellulose / N-ZnO heterojunction NO2 sensor, its preparation method and application
Patent Information
- Application Number
- CN202611012312.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-08
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]为解决或部分解决相关技术中存在的问题,本发明提出一种纤维素/N-ZnO异质结NO2传感器及其制备方法与应用,通过纤维素的三维多孔结构抑制N-ZnO纳米颗粒团聚、增大活性比表面积,并借助其表面官能团与N-ZnO形成的界面协同效应,显著提升传感器的响应灵敏度与稳定性,解决了传统ZnO基气体传感器所存在的工作温度高、抗湿性弱、柔韧性不足以及本征灵敏度有限等问题
在本发明的复合体系中,氮掺杂通过调控ZnO的电子结构,引入缺陷态与活性位点,有效增强了材料对NO2的电子捕获能力和表面反应活性,为降低工作温度、提升本征灵敏度奠定了基础。同时,纤维素纳米纤维凭借其三维多孔网络结构,不仅作为理想载体抑制了N-ZnO纳米颗粒的团聚,显著增加了复合材料的活性比表面积,还为NO2气体的扩散与吸附提供了高效通道;其表面丰富的羟基等官能团,可通过氢键等作用与N-ZnO紧密耦合,形成稳定的异质界面。该界面能进一步优化载流子传输路径,促进NO2吸附/脱附过程中的电荷转移,从而协同提升响应速度、灵敏度与信号稳定性。此外,纤维素赋予的柔性特质与N-ZnO的掺杂改性相结合,二者协同显著提升了传感器对NO2的吸附容量与反应动力学,实现器件在较低工作温度下对NO2的高灵敏检测,并兼具良好的机械柔性与环境友好性,为发展新一代高性能、柔性化NO2气体传感器提供了颇具潜力的材料体系。
Smart Images

Figure CN122962074A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanocomposite materials technology, specifically relating to a cellulose / N-ZnO heterojunction NO2 sensor, its preparation method, and its application. Background Technology
[0002] Cellulose, as a widely available and renewable natural polymer, has attracted widespread attention due to its unique structural properties and green sustainability. Cellulose nanofibers possess a three-dimensional network structure, high specific surface area, abundant surface functional groups (such as hydroxyl groups), and good mechanical flexibility, providing ideal conditions for their application in the sensing field. Their porous structure and high surface activity enable them not only to serve as a supporting framework for loading functional materials but also to promote the adsorption and diffusion of gas molecules, offering potential for constructing high-performance, flexible gas sensors.
[0003] Zinc oxide (ZnO), a typical n-type wide-bandgap semiconductor material, possesses numerous inherent defects, such as oxygen vacancies and zinc interstitials. It has been widely used for detecting harmful gases such as nitrogen oxides (e.g., NO2). However, intrinsic ZnO-based gas sensors still face significant limitations in practical applications: First, the optimal operating temperature of ZnO is typically high, leading to high energy consumption, decreased device stability, and difficulty in applying it to flexible and wearable systems; second, ZnO generally exhibits poor gas selectivity, making it susceptible to interference from environmental humidity and other gases; furthermore, ZnO nanoparticles are prone to aggregation, reducing active sites, and the material itself is relatively brittle, hindering the fabrication of flexible devices. Summary of the Invention
[0004] To address or partially resolve the problems existing in related technologies, this invention proposes a cellulose / N-ZnO heterojunction NO2 sensor, its preparation method, and its applications. By utilizing the three-dimensional porous structure of cellulose to suppress the aggregation of N-ZnO nanoparticles and increase the active specific surface area, and through the synergistic effect of the interface formed between cellulose's surface functional groups and N-ZnO, the sensor's response sensitivity and stability are significantly improved. This solves the problems of high operating temperature, weak moisture resistance, insufficient flexibility, and limited intrinsic sensitivity inherent in traditional ZnO-based gas sensors. Thus, a NO2 gas sensor with high sensitivity, low-temperature operation, good flexibility, and environmental friendliness is obtained, suitable for practical applications such as wearable devices and indoor environmental monitoring.
[0005] This invention provides a method for preparing a cellulose / N-ZnO heterojunction NO2 sensor, comprising the following steps: (1) Photolithography is performed on the substrate to obtain interdigitated electrode patterns; (2) A metal thin film is deposited on the interdigitated electrode pattern using metal thin film deposition technology to obtain a patterned metal / substrate structure sensor; (3) Nitrogen-doped zinc oxide nanomaterials were prepared by sol-gel method. The nitrogen-doped zinc oxide nanomaterials were uniformly mixed with cellulose nanofiber dispersion, and then dried to obtain three-dimensional porous composite aerogel. Finally, calcination was carried out to obtain cellulose / N-ZnO composite. (4) The cellulose / N-ZnO composite was dispersed in an organic solvent to obtain a dispersion. The dispersion was directly written onto the electrode sensitive area of the patterned metal / substrate structure sensor using an electro-spraying technique. Finally, the NO2 sensor was prepared by annealing.
[0006] In this invention, the introduction of nitrogen partially substitutes oxygen lattice sites in the ZnO wurtzite lattice, forming N2O ... o Acceptor defects, accompanied by the generation of oxygen vacancies (V). o ) and zinc gap (Zn iIntrinsic defects such as cellulose and N-ZnO nanoparticles alter the local coordination structure and electronic state density of ZnO, forming a high density of unsaturated coordinated Zn atoms and dangling bonds on the surface, providing highly active centers for the chemisorption of gas molecules. In the composite system of this invention, a highly efficient and synergistic organic-inorganic interface is constructed between the cellulose network and N-ZnO nanoparticles through multiple structural interactions: multidirectional hydrogen bond networks (O—H···O—Zn, O—H···N—Zn) and surface coordination bonds (Zn←OH—cellulose) are formed between the hydroxyl groups on the cellulose surface and the lattice oxygen, nitrogen doping sites, and unsaturated Zn atoms on the N-ZnO surface, firmly confining the N-ZnO nanoparticles to the fiber surface and network pores in a multi-point anchoring manner. This structural confinement effect effectively inhibits the aggregation and excessive grain growth of N-ZnO nanoparticles, ensuring that the active specific surface area is fully maintained. Furthermore, the organic-inorganic interface can further optimize carrier transport paths and promote charge transfer during NO2 adsorption / desorption, thereby synergistically improving response speed, sensitivity, and signal stability. Simultaneously, the cellulose three-dimensional network itself constructs interconnected macropores (>50 nm) and mesopores (2–50 nm) hierarchical channels, which, together with the micropores (<2 nm) formed between N-ZnO grains, constitute a multi-level porous system—macropores provide high-speed paths for rapid diffusion of gas molecules, mesopores increase the probability of contact between gas and the sensitive material, and micropores and interface defect sites serve as high-energy adsorption terminals. From the perspective of gas molecule dynamics, this multi-level porous structure can produce a sieving effect on gas molecules with different moving diameters. The throughput of larger moving diameter interfering gas molecules (such as volatile organic compounds like ethanol and acetone) in the mesopore and micropore regions is significantly lower than that of smaller moving diameter NO2 molecules (dynamic diameter approximately 0.35 nm), thus endowing the sensor with intrinsic selectivity advantages at the structural level. The flexible framework of the cellulose network can effectively buffer the lattice strain generated on the N-ZnO surface during NO2 adsorption / desorption, avoiding cracking and performance degradation of the sensitive film and ensuring the long-term cycling stability of the sensor. Based on the synergistic effects of hydrogen bond anchoring confinement, multi-level pore transport, size sieving, and stress buffering, the cellulose / N-ZnO heterojunction composite material achieves highly sensitive and rapid NO2 detection at lower operating temperatures, effectively overcoming the limitations of traditional ZnO-based sensors such as high operating temperature and slow response / recovery speed.
[0007] Preferably, the substrate is a silicon oxide wafer, a quartz wafer, a ceramic wafer, or a glass wafer, and the thickness of the substrate is 400-600 nm, wherein the oxide layer thickness of the silicon oxide wafer is 90-300 nm.
[0008] Preferably, the photolithography uses AZ5214 photoresist, AZ300 developer, and a URE-2000 / 35L ultraviolet depth lithography machine.
[0009] Preferably, the metal thin film deposition technology is magnetron sputtering deposition, thermal evaporation deposition, electroplating deposition, vacuum ion evaporation deposition, or electron beam evaporation deposition; the metal is Pt, Pb, Au, Ag, Ti, Ni, Al, Cu, or Co; and the thickness of the metal thin film is 20-150 nm.
[0010] Preferably, in step (2), the sol-gel method specifically includes: S1: Dissolve the zinc source in ethanol, then add oxalic acid and urea and continue stirring until a uniform gel is formed; S2: Dry the gel to obtain a dry gel, then calcine it and let it cool naturally to obtain nitrogen-doped zinc oxide nanomaterials.
[0011] Preferably, the zinc source is zinc acetate; the mass ratio of zinc source, oxalic acid and urea is (100-200):(50-150):(6-24).
[0012] Preferably, step S1 is performed at 60-90°C.
[0013] Preferably, in step S2, the calcination is carried out at 500-600°C for 2 hours in an air atmosphere.
[0014] Preferably, the mass ratio of the nitrogen-doped zinc oxide nanomaterial to the cellulose nanofiber is 100:(5-15), and the liquid solvent of the cellulose nanofiber dispersion is water.
[0015] Preferably, in step (3), the calcination temperature is 300-600℃, the time is 1-2 hours, and the atmosphere is an inert gas.
[0016] Preferably, in step (4), the organic solvent is a mixture of PVP, DMF and ethanol, wherein the volume ratio of PVP, DMF and ethanol is (0.5-1.5):(5-7):(0-2).
[0017] Preferably, the substrate stage heating temperature of the electro-inking technology is 30-60℃, the nozzle-to-substrate distance is 50-150mm, the operating DC voltage is 6.5-8.5KV, the injection pump propulsion flow rate is 0.5-5.0μL / s, the XY displacement motor speed is 0.5-5.0mm / s, and the XY displacement motor step size is 1.0-5.0mm / s.
[0018] Preferably, in step (4), the annealing temperature is 500°C, the time is 1 hour, and the atmosphere is an inert gas.
[0019] This invention utilizes electro-high-density printing (EHD) technology to prepare sensitive thin films, offering significant advantages over traditional drop-coating and spin-coating methods. This method enables patterned deposition with micron-level precision, boasts high material utilization, and can be directly formed on complex or flexible substrates. The prepared films exhibit uniform thickness, controllable pore structure, and strong adhesion to the substrate, avoiding the coffee ring effect of drop-coating and the limitations imposed on substrate shape by spin-coating. This provides a reliable solution for manufacturing high-performance, customized flexible sensors.
[0020] The present invention also claims protection for the cellulose / N-ZnO heterojunction NO2 sensor prepared by the method of preparing the cellulose / N-ZnO heterojunction NO2 sensor.
[0021] The present invention also claims protection for the application of the cellulose / N-ZnO heterojunction NO2 sensor in the detection of nitrogen dioxide gas.
[0022] The technical solution provided by this invention has the following beneficial effects: In the composite system of this invention, nitrogen doping, by modulating the electronic structure of ZnO and introducing defect states and active sites, effectively enhances the material's electron capture ability for NO2 and its surface reactivity, laying the foundation for lowering the operating temperature and improving intrinsic sensitivity. Simultaneously, cellulose nanofibers, with their three-dimensional porous network structure, not only act as an ideal carrier to inhibit the aggregation of N-ZnO nanoparticles and significantly increase the active specific surface area of the composite material, but also provide efficient channels for the diffusion and adsorption of NO2 gas. Their abundant hydroxyl and other functional groups on the surface can tightly couple with N-ZnO through hydrogen bonding and other interactions, forming a stable heterogeneous interface. This interface can further optimize the carrier transport path and promote charge transfer during NO2 adsorption / desorption, thereby synergistically improving response speed, sensitivity, and signal stability. Furthermore, the combination of the flexibility imparted by cellulose and the doping modification of N-ZnO significantly enhances the adsorption capacity and reaction kinetics of the sensor for NO2, enabling the device to detect NO2 with high sensitivity at lower operating temperatures. It also possesses good mechanical flexibility and environmental friendliness, providing a promising material system for the development of a new generation of high-performance, flexible NO2 gas sensors. Attached Figure Description
[0023] Figure 1 A schematic diagram of the fabrication process for a cellulose / N-ZnO heterojunction NO2 sensor.
[0024] Figure 2 This is a fabrication process diagram for a cellulose / N-ZnO heterojunction NO2 sensor.
[0025] Figure 3 A schematic diagram for EHD printing.
[0026] Figure 4This is a structural diagram of a cellulose / N-ZnO heterojunction NO2 sensor device. 100: silicon oxide wafer; 200: metal; 300: cellulose / N-ZnO.
[0027] Figure 5 Top view of a cellulose / N-ZnO heterojunction NO2 sensor device.
[0028] Figure 6 The sensor prepared in Example 1, a cellulose / N-ZnO heterojunction NO2 sensor, is shown in the device sensitivity-NO2 concentration characteristic curves under room temperature and ultraviolet light conditions.
[0029] Figure 7 The sensor prepared for Comparative Example 2 is shown in the device sensitivity-NO2 concentration characteristic curves under room temperature and ultraviolet light conditions.
[0030] Figure 8 The repeatability test curve of the cellulose / N-ZnO heterojunction NO2 sensor prepared in Example 1 at 1ppm NO2.
[0031] Figure 9 The image shows the long-term stability curve of the cellulose / N-ZnO heterojunction NO2 sensor prepared in Example 1 at 1 ppm NO2. Detailed Implementation
[0032] To better understand the technical content of this invention, specific embodiments are provided below to further illustrate this invention.
[0033] Example 1 like Figure 1 and 2 A method for preparing a cellulose / N-ZnO heterojunction NO2 sensor includes the following steps: (1) Photolithography is performed on a silicon oxide substrate to obtain interdigitated electrode patterns.
[0034] S1-1: Take a 500nm thick silicon oxide as the substrate, and the oxide layer thickness is 300nm.
[0035] S1-2: Place the silicon oxide wafer in a spin coater and add AZ5214 negative photoresist evenly on the silicon oxide wafer. Set the rotation speed and time as follows: rotate at a low speed of 450r for 10s, and then rotate at a high speed of 4000r for 40s. The photoresist thickness after spin coating is 1.4um.
[0036] S1-3: The silicon oxide wafer with a layer of negative photoresist is then heated on a 100°C heating plate for 90 seconds, followed by 4 seconds of exposure in a URE-2000 / 35L ultraviolet depth lithography machine, and then the silicon wafer is heated on a 115°C heating plate for 120 seconds.
[0037] S1-4: Perform another 4s general exposure. After exposure, place the silicon oxide wafer in AZ300 developer for 40s, then rinse with deionized water 4-5 times to remove excess developer. This will give you a substrate with interdigitated electrode patterns.
[0038] (2) A metal thin film was deposited on the surface of the substrate with electrode pattern using magnetron sputtering technology. The film was sputtered at a constant power of 90W for 3 minutes at room temperature to deposit a Ti layer of about 20nm as an adhesion layer. Then, Au of about 90nm was deposited as an electrode using a constant power of 64W for 3 minutes at 105℃ to obtain a patterned metal / substrate structure sensor device.
[0039] (3) Nitrogen-doped zinc oxide nanomaterials were prepared by the sol-gel method. The nitrogen-doped zinc oxide nanomaterials were uniformly mixed with cellulose nanofiber dispersion, and then dried to obtain a three-dimensional porous composite aerogel. Finally, the cellulose / N-ZnO composite was obtained by calcination. S3-1: Dissolve 429 mg of zinc acetate dihydrate [Zn(Ac)2·2H2O] in 20 ml of ethanol and stir at 60 °C for 1 h.
[0040] S3-2: Add 252 mg of oxalic acid dihydrate C2H2O4·2H2O and 30 mg of urea [CO(NH2)2] to the solution from the previous step, and continue stirring at 60°C for 30 min until a uniform gel is formed.
[0041] S3-3: Place the gel in an 80℃ oven and dry for 20 hours to obtain a dry gel.
[0042] S3-4: After grinding the dry gel, place it in a CVD chamber and calcine it at 500°C in air for 2 hours. After natural cooling, nitrogen-doped zinc oxide nanomaterials: N-ZnO powder can be obtained.
[0043] S3-5: Add 100 mg of N-ZnO powder to 1 ml of nanocellulose dispersion (concentration: 1 wt%, diameter: ~15-25 nm, solvent: water) and sonicate it for 1 h. Then transfer the suspension to a petri dish, centrifuge the suspension and dry it in a vacuum drying device at 80 °C for 24 h to obtain cellulose / N-ZnO composite material.
[0044] S3-6: The dried cellulose / N-ZnO composite material was ground and placed in a CVD reactor, calcined at 500℃ for 1 hour under an argon atmosphere. After cooling to room temperature, the following was weighed... 100 mg of sample was added to a mixed solvent of 6 ml DMF, 1.0 g PVP, and 1.5 ml ethanol. Subsequently, it was fully and uniformly redispersed by ultrasonic treatment and magnetically stirred for 10 h to finally form a stable cellulose / N-ZnO composite dispersion (i.e., the precursor slurry required for EHD printing).
[0045] (4) such as Figure 3 The NO2 sensor was fabricated by directly writing a cellulose / N-ZnO composite dispersion onto the sensitive area of the electrode using electro-inking technology. S4-1: The patterned metal / substrate structure sensor device (i.e., a substrate with electrodes) is fixed as a receiver on the substrate stage of the EHD printer.
[0046] S2: Fix the syringe containing the test solution (cellulose / N-ZnO composite dispersion) onto the Z-axis adjustable nozzle clamp, and adjust the clamp to keep the top of the syringe piston rod horizontally aligned with the bottom of the injection pump push rod. The syringe needle has an inner diameter of 0.16 mm and an outer diameter of 0.31 mm.
[0047] S3: Connect the positively charged wire of the high-voltage power supply to the nozzle, and connect the ground wire to the EHD substrate stage.
[0048] S4: Turn on the EHD main power and control power in sequence.
[0049] S5: Adjust the angle between the axis of the observation camera and the axis of the light to approximately 70-120° so that the PC can obtain a better observation angle.
[0050] S6: Obtain the distance between the needle tip and the center of the camera's field of view by observing the camera, and perform X and Y axis coordinate compensation to correct alignment errors.
[0051] S7: Turn on the high voltage power supply and the heating source. Set the substrate stage heating temperature to 40℃. Adjust the nozzle-to-substrate distance (opposition distance) to 73mm. Apply the working DC voltage to 7.2KV. Set the injection pump flow rate to 0.5μL / s. Write the G code for the desired printing pattern and burn the G code into the software. Set the XY platform to move at a speed of 1.0 mm / s along the preset pattern path. Set the XY displacement motor step size to 1.0 mm / s. Perform high-resolution patterned deposition of the composite material onto the sensitive area of the electrode.
[0052] S8: After the current substrate solution has been deposited, first turn off the high-voltage power supply, then turn off the PC terminal, control power supply, and main power supply. Afterwards, anneal at 500℃ for 1 hour in an inert atmosphere to obtain the desired result. Figure 4 and 5 The cellulose / N-ZnO heterojunction NO2 sensor shown.
[0053] Example 2 A method for preparing a cellulose / N-ZnO heterojunction NO2 sensor includes the following steps: (1) Photolithography is performed on a silicon oxide substrate to obtain interdigitated electrode patterns.
[0054] S1-1: Take a 400nm thick silicon oxide sheet as the substrate, and the oxide layer thickness is 200nm.
[0055] S1-2: Place the silicon oxide wafer in a spin coater and add AZ5214 negative photoresist evenly on the silicon oxide wafer. Set the rotation speed and time as follows: rotate at a low speed of 450r for 10s, and then rotate at a high speed of 4000r for 40s. The photoresist thickness after spin coating is 1.4um.
[0056] S1-3: The silicon oxide wafer with a layer of negative photoresist is then heated on a 100°C heating plate for 90 seconds, followed by 4 seconds of exposure in a URE-2000 / 35L ultraviolet depth lithography machine, and then the silicon wafer is heated on a 115°C heating plate for 120 seconds.
[0057] S1-4: Perform another 4s general exposure. After exposure, place the silicon oxide wafer in AZ300 developer for 40s, then rinse with deionized water 4-5 times to remove excess developer. This will give you a substrate with interdigitated electrode patterns.
[0058] (2) A metal thin film was deposited on the substrate surface with electrode pattern using magnetron sputtering technology. The film was sputtered at a constant power of 90W for 3 minutes at room temperature to deposit a Ti layer of about 20 nm as an adhesion layer. Then, a Pt layer of 20 nm thickness was deposited as an electrode by sputtering at a constant power of 95W for 5 minutes to obtain a patterned metal / substrate structure sensor device.
[0059] (3) Nitrogen-doped zinc oxide nanomaterials were prepared by the sol-gel method. The nitrogen-doped zinc oxide nanomaterials were uniformly mixed with cellulose nanofiber dispersion, and then dried to obtain a three-dimensional porous composite aerogel. Finally, the cellulose / N-ZnO composite was obtained by calcination. S3-1: Dissolve 100 mg of zinc acetate dihydrate [Zn(Ac)2·2H2O] in 20 ml of ethanol and stir at 60 °C for 1 h.
[0060] S3-2: Add 150 mg of oxalic acid dihydrate C2H2O4·2H2O and 24 mg of urea [CO(NH2)2] to the solution from the previous step, and continue stirring at 60°C for 30 min until a uniform gel is formed.
[0061] S3-3: Place the gel in an oven at 80℃ and dry for 20 hours to obtain a dry gel.
[0062] S3-4: After grinding the dry gel, place it in a CVD chamber and calcine it at 600℃ in air for 2 hours. After natural cooling, nitrogen-doped zinc oxide nanomaterials: N-ZnO powder can be obtained.
[0063] S3-5: Add 100 mg of N-ZnO powder to 1 ml of nanocellulose dispersion (concentration: 0.5 wt%, diameter: ~15-25 nm, solvent: water) and sonicate it for 1 h. Then transfer the suspension to a petri dish, centrifuge the suspension and dry it in a vacuum drying device at 80 °C for 24 h to obtain cellulose / N-ZnO composite material.
[0064] S3-6: The dried cellulose / N-ZnO composite material was ground and placed in a CVD reactor, calcined at 600℃ for 2 hours under an argon atmosphere. After cooling to room temperature, 200 mg of the sample was weighed and added to a mixed solvent of 5 ml DMF, 0.5 g PVP, and 1 ml ethanol. Subsequently, it was sonicated to fully and uniformly redisperse the mixture, and then magnetically stirred for 10 hours to finally form a stable cellulose / N-ZnO composite dispersion (i.e., the precursor slurry required for EHD printing).
[0065] (4) such as Figure 3 The NO2 sensor was fabricated by directly writing a cellulose / N-ZnO composite dispersion onto the sensitive area of the electrode using electro-inking technology. S4-1: The patterned metal / substrate structure sensor device (i.e., a substrate with electrodes) is fixed as a receiver on the substrate stage of the EHD printer.
[0066] S2: Fix the syringe containing the test solution (cellulose / N-ZnO composite dispersion) onto the Z-axis adjustable nozzle clamp, and adjust the clamp to keep the top of the syringe piston rod horizontally aligned with the bottom of the injection pump push rod. The syringe needle has an inner diameter of 0.16 mm and an outer diameter of 0.31 mm.
[0067] S3: Connect the positively charged wire of the high-voltage power supply to the nozzle, and connect the ground wire to the EHD substrate stage.
[0068] S4: Turn on the EHD main power and control power in sequence.
[0069] S5: Adjust the angle between the axis of the observation camera and the axis of the light to approximately 70-120° so that the PC can obtain a better observation angle.
[0070] S6: Obtain the distance between the needle tip and the center of the camera's field of view by observing the camera, and perform X and Y axis coordinate compensation to correct alignment errors.
[0071] S7: Turn on the high voltage power supply and the heating source. Set the substrate stage heating temperature to 60℃. Adjust the nozzle-to-substrate distance (opposition distance) to 75mm. Apply the working DC voltage to 7.3KV. Set the injection pump flow rate to 0.5μL / s. Write the G code for the desired printing pattern. Burn the G code into the software. Set the XY platform to move at a speed of 1 mm / s along the preset pattern path. Set the XY displacement motor step size to 1.0mm / s. Perform high-resolution patterned deposition of the composite material onto the sensitive area of the electrode.
[0072] S8: After the current substrate solution is deposited, first turn off the high voltage power supply, then turn off the PC terminal, control power supply and main power supply, and then anneal at 500℃ for 1 hour in an inert atmosphere to obtain the cellulose / N-ZnO heterojunction NO2 sensor.
[0073] Example 3 A method for preparing a cellulose / N-ZnO heterojunction NO2 sensor includes the following steps: (1) Photolithography is performed on a silicon oxide substrate to obtain interdigitated electrode patterns.
[0074] S1-1: Take a 600nm thick silicon oxide sheet as the substrate, and the oxide layer thickness is 90nm.
[0075] S1-2: Place the silicon oxide wafer in a spin coater and add AZ5214 negative photoresist evenly on the silicon oxide wafer. Set the rotation speed and time as follows: rotate at a low speed of 450r for 10s, and then rotate at a high speed of 4000r for 40s. The photoresist thickness after spin coating is 1.4um.
[0076] S1-3: The silicon oxide wafer with a layer of negative photoresist is then heated on a 100°C heating plate for 90 seconds, followed by 4 seconds of exposure in a URE-2000 / 35L ultraviolet depth lithography machine, and then the silicon wafer is heated on a 115°C heating plate for 120 seconds.
[0077] S1-4: Perform another 4s general exposure. After exposure, place the silicon oxide wafer in AZ300 developer for 40s, then rinse with deionized water 4-5 times to remove excess developer. This will give you a substrate with interdigitated electrode patterns.
[0078] (2) A metal thin film was deposited on the substrate surface with electrode pattern using magnetron sputtering technology. The sputtering was performed at a constant power of 90W for 3 minutes at room temperature to deposit a Ti layer of about 20 nm as an adhesion layer. Then, a Ni layer of 20 nm thickness was deposited as an electrode by sputtering at a constant power of 66W and a temperature of 100℃ for 3.5 minutes to obtain a patterned metal / substrate structure sensor device.
[0079] (3) Nitrogen-doped zinc oxide nanomaterials were prepared by the sol-gel method. The nitrogen-doped zinc oxide nanomaterials were uniformly mixed with cellulose nanofiber dispersion, and then dried to obtain a three-dimensional porous composite aerogel. Finally, the cellulose / N-ZnO composite was obtained by calcination. S3-1: Dissolve 429 mg of zinc acetate dihydrate [Zn(Ac)2·2H2O] in 20 ml of ethanol and stir at 60 °C for 1 h.
[0080] S3-2: Add 252 mg of oxalic acid dihydrate C2H2O4·2H2O and 6 mg of urea [CO(NH2)2] to the solution from the previous step, and continue stirring at 60°C for 30 min until a uniform gel is formed.
[0081] S3-3: Place the gel in an oven at 80℃ and dry for 20 hours to obtain a dry gel.
[0082] S3-4: After grinding the dry gel, place it in a CVD chamber and calcine it at 500°C in air for 2 hours. After natural cooling, nitrogen-doped zinc oxide nanomaterials: N-ZnO powder can be obtained.
[0083] S3-5: Add 100 mg of N-ZnO powder to 1 ml of nanocellulose dispersion (concentration: 1.5 wt%, diameter: ~15-25 nm, solvent: water) and sonicate it for 1 h. Then transfer the suspension to a petri dish, centrifuge the suspension and dry it in a vacuum drying device at 80 °C for 24 h to obtain cellulose / N-ZnO composite material.
[0084] S3-6: The dried cellulose / N-ZnO composite material was ground and placed in a CVD reactor, calcined at 300℃ for 1.5 h under an argon atmosphere. After cooling to room temperature, 50 mg of the sample was weighed and added to a mixed solvent of 7 ml DMF and 0.8 g PVP. Subsequently, it was ultrasonically treated to fully and uniformly redisperse the mixture, and magnetically stirred for 10 h to finally form a stable cellulose / N-ZnO composite dispersion (i.e., the precursor slurry required for EHD printing).
[0085] (4) such as Figure 3 The NO2 sensor was fabricated by directly writing a cellulose / N-ZnO composite dispersion onto the sensitive area of the electrode using electro-inking technology. S4-1: The patterned metal / substrate structure sensor device (i.e., a substrate with electrodes) is fixed as a receiver on the substrate stage of the EHD printer.
[0086] S2: Fix the syringe containing the test solution (cellulose / N-ZnO composite dispersion) onto the Z-axis adjustable nozzle clamp, and adjust the clamp to keep the top of the syringe piston rod horizontally aligned with the bottom of the injection pump push rod. The syringe needle has an inner diameter of 0.16 mm and an outer diameter of 0.31 mm.
[0087] S3: Connect the positively charged wire of the high-voltage power supply to the nozzle, and connect the ground wire to the EHD substrate stage.
[0088] S4: Turn on the EHD main power and control power in sequence.
[0089] S5: Adjust the angle between the axis of the observation camera and the axis of the light to approximately 70-120° so that the PC can obtain a better observation angle.
[0090] S6: Obtain the distance between the needle tip and the center of the camera's field of view by observing the camera, and perform X and Y axis coordinate compensation to correct alignment errors.
[0091] S7: Turn on the high voltage power supply and the heating source. Set the substrate stage heating temperature to 30℃. Adjust the nozzle-to-substrate distance (opposition distance) to 73mm. Apply the working DC voltage to 7.2KV. Set the injection pump flow rate to 0.5μL / s. Write the G code for the desired printing pattern and burn the G code into the software. Set the XY platform to move at a speed of 0.5 mm / s along the preset pattern path. Set the XY displacement motor step size to 1.0mm / s. Perform high-resolution patterned deposition of the composite material onto the sensitive area of the electrode.
[0092] S8: After the current substrate solution is deposited, first turn off the high voltage power supply, then turn off the PC terminal, control power supply and main power supply, and then anneal at 500℃ for 1 hour in an inert atmosphere to obtain the cellulose / N-ZnO heterojunction NO2 sensor.
[0093] Comparative Example 1 The only difference between the preparation method of the cellulose / ZnO composite NO2 sensor in this comparative example and Example 1 is that step (3) in this comparative example prepares ZnO instead of nitrogen-doped zinc oxide; the specific steps are as follows: (1) Electrode patterns are obtained by photolithography on a silicon oxide substrate: S1-1: Take a silicon oxide substrate with an oxide layer thickness of 300nm.
[0094] S1-2: Place the silicon oxide wafer in a spin coater and add AZ5214 negative photoresist evenly on the silicon oxide wafer. Set the rotation speed and time as follows: rotate at a low speed of 450r for 10s, and then rotate at a high speed of 4000r for 40s. The photoresist thickness after spin coating is 1.4um.
[0095] S1-3: The silicon oxide wafer with a layer of negative photoresist is then heated on a 100°C heating plate for 90 seconds, followed by 4 seconds of exposure in a URE-2000 / 35L ultraviolet depth lithography machine, and then the silicon wafer is placed on a 115°C heating plate and heated for 120 seconds. S1-4: Perform another 4s general exposure. After exposure, place the silicon oxide wafer in AZ300 developer for 40s, then rinse with deionized water 4-5 times to remove excess developer, and you will get a substrate with electrode patterns.
[0096] (2) A metal thin film is deposited on the surface of a substrate with an electrode pattern using magnetron sputtering technology. The film is sputtered at a constant power of 90W for 3 minutes at room temperature to deposit a Ti layer of about 20nm as an adhesion layer. Then, Au of about 90nm is deposited as a contact electrode by sputtering at a constant power of 64W for 3 minutes at 105℃ to obtain a patterned metal / substrate structure sensor device.
[0097] (3) Zinc oxide nanomaterials were prepared by the sol-gel method. Zinc oxide nanomaterials were uniformly mixed with cellulose nanofiber dispersion, then dried to obtain a three-dimensional porous composite aerogel, and finally calcined to obtain a cellulose / ZnO composite: S3-1: Dissolve 429 mg of zinc acetate dihydrate [Zn(Ac)2·2H2O] in 20 ml of ethanol and stir at 60 °C for 1 h.
[0098] S3-2: Add 252 mg of oxalic acid dihydrate C2H2O4·2H2O to the solution from the previous step, and continue stirring at 60℃ for 30 min until a uniform gel is formed.
[0099] S3-3: Place the gel in an oven at 80℃ and dry for 20 hours to obtain a dry gel.
[0100] S3-4: After grinding the dry gel, place it in a CVD chamber and calcine it at 500°C in air for 2 hours. After natural cooling, zinc oxide nanomaterials: ZnO powder can be obtained.
[0101] S3-5: Add 100 mg of ZnO powder to 1 ml of nanocellulose dispersion (concentration: 1 wt%, diameter: ~15-25 nm, water) and sonicate it for 1 h. Then transfer the suspension to a petri dish, centrifuge the suspension and dry it in a vacuum drying device at 80 °C for 24 h to obtain cellulose / ZnO composite material.
[0102] S3-6: The dried cellulose / ZnO composite material was ground and placed in a CVD reactor, calcined at 500℃ for 1 hour under an argon atmosphere. After cooling to room temperature, 100 mg of the sample was weighed and added to a mixed solvent of 6 ml DMF, 1.0 g PVP, and 1.5 ml ethanol. Subsequently, it was sonicated to fully and uniformly redisperse the mixture, and magnetically stirred for 10 hours to finally form a stable cellulose / ZnO composite dispersion (i.e., the precursor slurry required for EHD printing).
[0103] (4) The NO2 sensor was fabricated by directly writing the cellulose / ZnO composite dispersion onto the sensitive area of the electrode using electro-inking technology: S4-1: The patterned metal / substrate structure sensor device (i.e., a substrate with electrodes) is fixed as a receiver on the substrate stage of the EHD printer.
[0104] S2: Fix the syringe containing the test solution (cellulose / ZnO composite dispersion) onto the Z-axis adjustable nozzle clamp, and adjust the clamp to keep the top of the syringe piston rod and the bottom of the injection pump push rod horizontally aligned. The syringe needle has an inner diameter of 0.16 mm and an outer diameter of 0.31 mm.
[0105] S3: Connect the positively charged wire of the high-voltage power supply to the nozzle, and connect the ground wire to the EHD substrate stage.
[0106] S4: Turn on the EHD main power and control power in sequence.
[0107] S5: Adjust the angle between the axis of the observation camera and the axis of the light to approximately 70-120° so that the PC can obtain a better observation angle.
[0108] S6: Obtain the distance between the needle tip and the center of the camera's field of view by observing the camera, and perform X and Y axis coordinate compensation to correct alignment errors.
[0109] S7: Turn on the high voltage power supply and the heating source. Set the substrate stage heating temperature to 50℃. Adjust the nozzle-to-substrate distance (opposition distance) to 70mm. Apply the working DC voltage to 7.2KV. Set the injection pump flow rate to 0.5μL / s. Write the G code for the desired printing pattern and burn the G code into the software. Set the XY platform to move at a speed of 1.0mm / s along the preset pattern path. Set the XY displacement motor step size to 1.0mm / s. Perform high-resolution patterned deposition of the composite material onto the sensitive area of the electrode.
[0110] S8: After the current driving solution is deposited, first turn off the high voltage power supply, then turn off the PC terminal, control power supply and main power supply, and then anneal at 500℃ for 1 hour in an inert atmosphere to obtain the cellulose / ZnO composite NO2 sensor.
[0111] Comparative Example 2 This comparative example describes a method for preparing an N-ZnO composite NO2 sensor, with the specific steps as follows: (1) Electrode patterns are obtained by photolithography on a silicon oxide substrate: S1-1: Take a silicon oxide substrate with an oxide layer thickness of 300nm.
[0112] S1-2: Place the silicon oxide wafer in a spin coater and add AZ5214 negative photoresist evenly on the silicon oxide wafer. Set the rotation speed and time as follows: rotate at a low speed of 450r for 10s, and then rotate at a high speed of 4000r for 40s. The photoresist thickness after spin coating is 1.4um.
[0113] S1-3: The silicon oxide wafer with a layer of negative photoresist is then heated on a 100°C heating plate for 90 seconds, followed by 4 seconds of exposure in a URE-2000 / 35L ultraviolet depth lithography machine, and then the silicon oxide wafer is heated on a 115°C heating plate for 120 seconds. S1-4: Perform another 4s general exposure. After exposure, place the silicon oxide wafer in AZ300 developer for 40s, then rinse with deionized water 4-5 times to remove excess developer. This will give you a substrate with interdigitated electrode patterns.
[0114] (2) A metal thin film was deposited on the surface of the substrate with electrode pattern using magnetron sputtering technology. The film was sputtered at a constant power of 90W for 3 minutes at room temperature to deposit a Ti layer of about 20nm as an adhesion layer. Then, Au of about 90nm was deposited as an electrode using a constant power of 64W for 3 minutes at 105℃ to obtain a patterned metal / substrate structure sensor device.
[0115] (3) Nitrogen-doped zinc oxide nanomaterials were prepared using the sol-gel method: S3-1: Dissolve 429 mg of zinc acetate dihydrate [Zn(Ac)2·2H2O] in 20 ml of ethanol and stir at 60 °C for 1 h.
[0116] S3-2: Add 252 mg of oxalic acid dihydrate C2H2O4·2H2O and 30 mg of urea [CO(NH2)2] to the solution from the previous step, and continue stirring at 60°C for 30 min until a uniform gel is formed.
[0117] S3-3: Place the gel in an oven at 80℃ and dry for 20 hours to obtain a dry gel.
[0118] S3-4: After grinding the dry gel, place it in a CVD chamber and calcine it at 500°C in air for 2 hours. After natural cooling, nitrogen-doped zinc oxide nanomaterials: N-ZnO powder can be obtained.
[0119] S3-5: Weigh 100 mg of N-ZnO powder and add it to a mixed solvent of 6 ml DMF, 1.0 g PVP, and 1.5 ml ethanol. Then, sonicate the powder to fully and uniformly redisperse it, followed by magnetic stirring for 10 hours to finally form a stable N-ZnO dispersion (i.e., the precursor slurry required for EHD printing).
[0120] (4) The NO2 sensor was fabricated by directly writing the N-ZnO dispersion onto the sensitive area of the electrode using electro-inking technology: S4-1: The patterned metal / substrate structure sensor device (i.e., a substrate with electrodes) is fixed as a receiver on the substrate stage of the EHD printer.
[0121] S2: Fix the syringe containing the test solution (N-ZnO dispersion) onto the Z-axis adjustable nozzle clamp, and adjust the clamp to keep the top of the syringe piston rod horizontally aligned with the bottom of the injection pump push rod. The syringe needle has an inner diameter of 0.16 mm and an outer diameter of 0.31 mm.
[0122] S3: Connect the positively charged wire of the high-voltage power supply to the nozzle, and connect the ground wire to the EHD substrate stage.
[0123] S4: Turn on the EHD main power and control power in sequence.
[0124] S5: Adjust the angle between the axis of the observation camera and the axis of the light to approximately 70-120° so that the PC can obtain a better observation angle.
[0125] S6: Obtain the distance between the needle tip and the center of the camera's field of view by observing the camera, and perform X and Y axis coordinate compensation to correct alignment errors.
[0126] S7: Turn on the high voltage power supply and the heating source. Set the substrate stage heating temperature to 40℃. Adjust the nozzle-to-substrate distance (opposition distance) to 70mm. Apply the working DC voltage to 7.2KV. Set the injection pump flow rate to 0.8μL / s. Write the G code for the desired printing pattern. Burn the G code into the software. Set the XY platform to move at a speed of 1.0mm / s along the preset pattern path. Set the XY displacement motor step size to 1mm / s. Perform high-resolution patterned deposition of the composite material onto the sensitive area of the electrode.
[0127] S8: After the current driving solution is deposited, first turn off the high voltage power supply, then turn off the PC terminal, control power supply and main power supply, and then anneal at 500℃ for 1 hour in an inert atmosphere to obtain the N-ZnO NO2 sensor.
[0128] Example of effect 1 Comparison of NO2 sensing performance of sensors from Examples 1 (Au), 2 (Pt), and 3 (Ni): The Au electrode used in Example 1 is significantly superior to Examples 2 and 3 in terms of sensitivity, detection limit, response / recovery characteristics, and long-term stability. Example 1 has the highest response value to NO2 and the widest linear response range; although Example 2 has a faster response, it is prone to sensitivity saturation and incomplete recovery; Example 3 has the worst overall performance because the Ni surface is easily oxidized to form a NiO layer, resulting in increased contact resistance and severe baseline drift. Therefore, Au is the preferred electrode material for the sensor structure of this application. Studies have shown that compared with Comparative Example 1, the material prepared in Comparative Example 1 is significantly weaker in terms of sensitivity, detection limit, response / recovery characteristics, and long-term stability, indicating that appropriate N doping is beneficial for controlling the ZnO band structure, microstructure, and defect engineering, which is beneficial for enhancing the NO2 sensing performance.
[0129] Figure 6 , Figure 7 The figures show the sensitivity-NO2 concentration characteristic curves of the devices in Example 1 and Comparative Example 2 under room temperature and UV conditions, respectively. The sensitivity of the gas-sensitive element is defined as the ratio of its resistance Rg in NO2 gas to its resistance Ra in air. In this case, the sensitivities of Example 1 and Comparative Example 2 at 5 ppm NO2 are 12.95 and 2.89, respectively. This indicates that the high specific surface area of cellulose and its gas adsorption capacity, the interfacial regulation effect of the hydroxyl functional groups, and their synergistic effect with ZnO increase the surface chemical reaction of the detected gas (NO2) and form charge transfer between ZnO and cellulose, thereby effectively improving the sensor's sensitivity to NO2 and increasing the sensor's response by 4.5 times. Figure 8 The repeatability of the gas sensor in this embodiment is tested by injecting 1 ppm NO2 under ultraviolet light at room temperature, 70% humidity, and 365 nm. Figure 9 This is a 15-day long-term test of the embodiment, designed to evaluate the stability of the sensor's sensitivity. The overall data trend shows that the sensitivity remained at a high level (approximately 200%) in the initial stage (0-5 days), then gradually decreased, dropping to approximately 170-180% by day 10, and further decreasing to approximately 120-140% by days 11-14. The overall trend is a slow initial decline followed by a rapid decrease, but there is a slight rebound in the last few days, possibly due to measurement errors or environmental factors. Over the 15 days, the sensitivity decreased from approximately 210% to approximately 140%, an absolute decrease of approximately 7 percentage points and a relative decrease of approximately 33%. This indicates that the sensor experiences some performance degradation during long-term use, but still retains a certain degree of long-term stability.
[0130] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or improvement of the technology in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.
Claims
1. A method for preparing a cellulose / N-ZnO heterojunction NO2 sensor, characterized in that, Includes the following steps: (1) Photolithography is performed on the substrate to obtain interdigitated electrode patterns; (2) A metal thin film is deposited on the interdigitated electrode pattern using metal thin film deposition technology to obtain a patterned metal / substrate structure sensor; (3) Nitrogen-doped zinc oxide nanomaterials were prepared by sol-gel method. The nitrogen-doped zinc oxide nanomaterials were uniformly mixed with cellulose nanofiber dispersion, and then dried to obtain three-dimensional porous composite aerogel. Finally, calcination was carried out to obtain cellulose / N-ZnO composite. (4) The cellulose / N-ZnO composite was dispersed in an organic solvent to obtain a dispersion. The dispersion was directly written onto the electrode sensitive area of the patterned metal / substrate structure sensor using an electro-spraying technique. Finally, the NO2 sensor was prepared by annealing.
2. The method for preparing the cellulose / N-ZnO heterojunction NO2 sensor as described in claim 1, characterized in that, The substrate is a silicon oxide wafer, a quartz wafer, a ceramic wafer, or a glass wafer, with a thickness of 400-600 nm, wherein the oxide layer thickness of the silicon oxide wafer is 90-300 nm.
3. The method for preparing the cellulose / N-ZnO heterojunction NO2 sensor as described in claim 1, characterized in that, The metal thin film deposition technology is magnetron sputtering deposition, thermal evaporation deposition, electroplating deposition, vacuum ion evaporation deposition, or electron beam evaporation deposition; the metal thin film includes a bottom Ti film and an upper metal A film, wherein the metal A is Pt, Pb, Au, Ag, Ti, Ni, Al, Cu, or Co; the thickness of the metal thin film is 20-150 nm.
4. The method for preparing the cellulose / N-ZnO heterojunction NO2 sensor as described in claim 1, characterized in that, In step (2), the sol-gel method specifically includes: S1: Dissolve the zinc source in ethanol, then add oxalic acid dihydrate and urea and continue stirring until a uniform gel is formed; S2: Dry the gel to obtain a dry gel, then calcine it and let it cool naturally to obtain nitrogen-doped zinc oxide nanomaterials.
5. The method for preparing the cellulose / N-ZnO heterojunction NO2 sensor as described in claim 4, characterized in that, In step S1, the zinc source is zinc acetate or zinc nitrate pentahydrate, and the mass ratio of zinc source, oxalic acid dihydrate, and urea is (100-200):(50-150):(6-24). Step S1 is carried out at 60-90℃. In step S2, the calcination temperature is 500-600℃, the time is 2 hours, and the atmosphere is air.
6. The method for preparing the cellulose / N-ZnO heterojunction NO2 sensor as described in claim 1, characterized in that, In step (3), the mass ratio of nitrogen-doped zinc oxide nanomaterials to cellulose nanofibers is 100:(5-15); the calcination temperature is 300-600℃, the time is 1-2 hours, and the atmosphere is an inert gas.
7. The method for preparing the cellulose / N-ZnO heterojunction NO2 sensor as described in claim 1, characterized in that, In step (4), the organic solvent is a mixture of PVP, DMF and ethanol, wherein the volume ratio of PVP, DMF and ethanol is (0.5-1):(5-7):(0-2).
8. The method for preparing the cellulose / N-ZnO heterojunction NO2 sensor as described in claim 1, characterized in that, The substrate stage heating temperature of the electro-inking technology is 30-60℃, the nozzle-to-substrate distance is 50-150mm, the working DC voltage is 6.5-8.5KV, the injection pump flow rate is 0.5-5μL / s, the XY displacement motor speed is 0.5-10mm / s, and the XY displacement motor step size is 1.0-5.0mm / s; in step (4), the annealing temperature is 500℃, the time is 1 hour, and the atmosphere is inert gas.
9. The cellulose / N-ZnO heterojunction NO2 sensor prepared by the method of any one of claims 1-8.
10. The application of the cellulose / N-ZnO heterojunction NO2 sensor according to claim 9 in the detection of nitrogen dioxide gas.